A Portrayal of Heroism Values in a Literary Work of the Acehnese Heroine: Keumalahayati - Diana Fauzia Sari; Raudhatul Jannah; Yunisrina Qismullah Yusuf; Yuliana Natsir (Proceedings of AICS - Social Sciences, 2021)
This study is aimed at investigating the types of heroism values portrayed in an Acehnese heroine in the novel Perempuan Keumala by Endang Moerdopo. The descriptive qualitative research design was applied in conducting this literary research. By using documents and discourse analysis in the novel, the dialogues between the characters and descriptions of expressions and events were used to analyze the types of heroism values embedded in the main character. The results showed that all types of heroism values were found in this heroine. They are moral greatness (17 data), ability (18 data), action in the face of opposition (6 data), and triumph in spirituality (5 data). From those values, the ability was the dominant type possessed by the heroine. Her moral greatness comprised persistence, caring, surrender to Allah, sacrifice, and courage. In ability, she had fighting skills, seen by others as a special woman, could conduct her duties as a wife, mother, and a wise leader commanding incredible missions. Moreover, in action in the face of opposition, she always helped others in need and enforced the law responsibly. Finally, in triumph in spirituality, she achieved a great victory in defeating the enemy and brought glory to Aceh. These values are strongly related to the religion and culture of the Acehnese people. Therefore, by studying heroism values of a society through literary works, researchers can also understand the society’s wisdom of life and how they overcome struggles.Keywords: Heroism values, Acehnese history, Acehnese heroine, Keumalahayati.